Treat stroke to target trial design: First trial comparing two LDL targets in patients with atherothrombotic strokes. (September 2019) - Amarenco, Pierre; Kim, Jong S; Labreuche, Julien; Giroud, Maurice; Lee, Byung-Chul; Mahagne, Marie-Hélène; Nighoghossian, Norbert; Simon, Tabassome; Steg, Philippe Gabriel; Touboul, Pierre-Jean; Vicaut, Eric; Yelles, Nessima; et al.
Background: In patients with non-cardio-embolic stroke, atorvastatin 80 mg/day reduced the relative risk of recurrent stroke by 16%, and a post hoc analysis showed that achieving an LDL-c of less than 70 mg/dL reduced the relative risk by 28% as compared to an on-treatment LDL of 100 mg/dL or more. Current guidelines from the French drug agency recommend treating with a statin after an ischaemic stroke to a target of less than 100 mg/dL, but no study directly tested LDL-c targets. The Treat Stroke to Target (TST) trial will compare the efficacy of achieving an LDL-c of less than 70 mg/dL versus an achieved LDL-c of 100 ± 10 mg/dL for secondary prevention in patients with recent ischaemic stroke of atherosclerotic origin. Main hypothesis: An achieved on-treatment LDL-c of less than 70 mg/dL will reduce by 25% the risk of recurrent ischaemic stroke, myocardial infarction, urgent coronary or carotid revascularisation following new symptoms requiring hospitalisation, and vascular death compared with on-treatment LDL-c of 100 ± 10 mg/dL. Design: Patients are randomised to either LDL-c levels, and the investigator who is not blinded can use the lipid-lowering agent of his/her choice available on the market (including statins and ezetimibe), in order to achieve the assigned LDL-c level. To be eligible for enrolment, patients have a recent ischaemic stroke or TIA of atherosclerotic origin with at least one arterial stenosis of a cerebral artery, enrolled between acute phase of the qualifying stroke (once the neurological deficit is stabilised) and three months. The initial planned sample size of 3760 participants followed three years was amended to allow follow-up of all enrolled patients until 385 primary efficacy outcome events have occurred, and no later than 31 December 2019. Patients will be recruited in 76 sites in two countries (France and South Korea) between March 2010 and December 2018 (last included patient followed up to one year). Safety outcomes will include haemorrhagic strokes and new onset diabetes. All primary endpoints will be adjudicated by an endpoint committee, blinded to the assigned LDL-c level. Two sub-studies assess (1) the relative effect of assigned LDL-c levels on occurrence of new atherosclerotic plaque as detected by carotid ultrasound during follow-up, using M'ATH software for repositioning and (2) the genetic and biomarker drivers of recurrent primary endpoints according to assigned LDL-c lowering arm, in atherosclerotic strokes. Summary: The TST trial is evaluating the benefits of achieving an LDL-c less than 70 mg/dL for secondary stroke prevention in ischaemic stroke patients of atherosclerotic origin. Main results are anticipated in 2020 or earlier (ClinicalTrials.gov NCT01252875).